2012
DOI: 10.1111/j.1475-097x.2012.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

Time under tension decreased with blood flow–restricted exercise

Abstract: These results may benefit populations that cannot sustain the mechanical stress of high-intensity exercise or low-intensity exercise that requires a longer sustained time under tension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 39 publications
1
33
0
1
Order By: Relevance
“…The authors found that both conditions similarly elevated HR to approximately 200 b$min21 at 10 seconds postexercise. Furthermore, Loenneke et al (54) observed similar HR responses during 2 sets of bilateral knee extensions to failure, at 30% of 1RM with BFR via elastic knee wraps and without BFR. Collectively, these findings indicate that an increased HR response may be inevitable with or without BFR when exercise is performed to repetition failure.…”
mentioning
confidence: 75%
“…The authors found that both conditions similarly elevated HR to approximately 200 b$min21 at 10 seconds postexercise. Furthermore, Loenneke et al (54) observed similar HR responses during 2 sets of bilateral knee extensions to failure, at 30% of 1RM with BFR via elastic knee wraps and without BFR. Collectively, these findings indicate that an increased HR response may be inevitable with or without BFR when exercise is performed to repetition failure.…”
mentioning
confidence: 75%
“…Several studies using BFR in combination with low load resistance exercise have observed increases in WBL (15,26,40). The accumulation of this lactate along with other metabolites has been hypothesized to play an important role in skeletal muscle adaptation through increased muscle fiber recruitment (20).…”
Section: Whole Bood Lactatementioning
confidence: 99%
“…Participants cycled at 202 (36), 97 (26), and 97 (26) watts during the High, 40BFR, and 60BFR conditions. The wattage used during exercise was significantly higher in the High compared to the other conditions (p < 0.001).…”
Section: Exercise Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As associações entre o treino de oclusão vascular e o lactato sanguíneo tem sido discutido quando se trata de controle de intensidade de treino e a relação desta intensidade com processos metabólicos específicos (Gil et al, 2015;Loenneke, Wilson, Balapur, et al, 2012;Yasuda et al, 2014). No nosso estudo, ficou evidente que o treino sob oclusão vascular induziu aumentos significativos do lactato sanguíneo em diferentes momentos (meio e final do treino) quando comparados aos valores basais, bem como no grupo que treinou sob alta intensidade, que apesar de não ter sido observada a significância, observou-se valores altos de lactato.…”
Section: Análise Estatísticaunclassified